Water‐Use Data in the United States: Challenges and Future Directions. (10th May 2022) - Marston, Landon T.; Abdallah, Adel M.; Bagstad, Kenneth J.; Dickson, Kerim; Glynn, Pierre; Larsen, Sara G.; Melton, Forrest S.; Onda, Kyle; Painter, Jaime A.; Prairie, James; Ruddell, Benjamin L.; Rushforth, Richard R.; et al.
Abstract: In the United States, greater attention has been given to developing water supplies and quantifying available waters than determining who uses water, how much they withdraw and consume, and how and where water use occurs. As water supplies are stressed due to an increasingly variable climate, changing land‐use, and growing water needs, greater consideration of the demand side of the water balance equation is essential. Data about the spatial and temporal aspects of water use for different purposes are now critical to long‐term water supply planning and resource management. We detail the current state of water‐use data, the major stakeholders involved in their collection and applications, and the challenges in obtaining high‐quality nationally consistent data applicable to a range of scales and purposes. Opportunities to improve access, use, and sharing of water‐use data are outlined. We cast a vision for a world‐class national water‐use data product that is accessible, timely, and spatially detailed. Our vision will leverage the strengths of existing local, state, and federal agencies to facilitate rapid and informed decision‐making, modeling, and science for water resources. To inform future decision‐making regarding water supplies and uses, we must coordinate efforts to substantially improve our capacity to collect, model, and disseminate water‐use data. Abstract : Research Impact Statement : To inform future decision‐making regarding water supplies and uses, we must coordinate efforts to substantially improve our capacity to collect, model, and disseminate water‐use data.